Peran manajemen risiko pembiayaan syariah pada nasabah generasi z dengan pola konsumsi digital - Azizah, Alfia Nur (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has significantly transformed Islamic banking in Indonesia, particularly in shaping the behavior of Generation Z customers who prioritize convenience and efficiency. This study aims to analyze the role of risk management in Islamic financing concerning Generation Z characteristics in the digital era. The method used is a qualitative approach through literature review from various relevant sources. The results indicate that Generation Z tends to exhibit consumptive and impulsive behavior, along with relatively low Islamic financial literacy, which increases financing risks, especially the potential for Non-Performing Financing (NPF). From an Islamic perspective, risk management must be conducted in a balanced manner by avoiding elements of riba, maysir, gharar, and ghish. Therefore, optimal risk management implementation is required through strict financing analysis, continuous monitoring, and improving Islamic financial literacy. These efforts are expected to minimize financing risks while encouraging Generation Z to make more prudent financial decisions in accordance with sharia principles.